Campaign Effects in a Changing Environment: The 2006 Italian Legislative Elections - Lisi, Marco (2015)
Studies on elections and voting behavior have generally shown that campaigns display only a minimal effect, while predispositions are found to play a fundamental role in influencing voters' preferences. This paper aims to re-evaluate these findings by analyzing campaign effects through a panel survey conducted during the 2006 Italian elections. This case study is particularly interesting due to the changes in the political and media environment that occurred after the mid-1990s. The results substantially confirm that campaign-related variables have a weak impact on voting choice, although they had important effects in terms of voters' participation and floating voters' orientations.